Relationships in late life from a personal communities approach: perspectives of older people in Chile. Issue 5 (15th May 2022) - Torrejon, Maria-Jose; Martin-Matthews, Anne
Abstract: Although the literature on social capital, social support and social networks uses the concept of emotional support, studies rarely recognise nuances of the emotional relationships in late life. Using a personal communities framework, we examine the subjective meaning of family and friendship ties that form the network of emotionally close relationships of a cohort of Chilean people between 60 and 74 years of age. Chile is an interesting case to investigate personal communities, as the country is facing both a rapid process of population ageing and the consequences of abrupt socio-cultural changes triggered by a military government. We conducted qualitative semi-structured interviews using personal communities diagrams that enabled study participants to reflect on what and how different types of personal ties were important to them. Data analysis included thematic analysis of interview transcripts and classification of identified personal communities using Pahl and Spencer's typology. The personal communities framework proved useful in capturing the composition of older people's networks of close relationships and in reflecting the diverse ways different ties are relevant in late life. We further developed a complementary typology based on the distinction between 'clustered' and 'hierarchical' personal communities. This complementary typology adds a cultural dimension to understand better emotional closeness in late life in a context of rapid socio-cultural changes affecting levels of social trust.